A reappraisal of generic bisphosphonates in osteoporosis. - Kanis, J; Reginster, J; Kaufman, J; Ringe, J; Adachi, J; Hiligsmann, M; Rizzoli, R; Cooper, C (2012)
UNLABELLED: The competitive price of generic bisphosphonates has had a marked effect on practice guidelines, but an increasing body of evidence suggests that they have more limited effectiveness than generally assumed. INTRODUCTION: The purpose of this study is to review the impact of generic bisphosphonates on effectiveness in the treatment of osteoporosis. METHODS: This study is a literature review. RESULTS: A substantial body of evidence indicates that many generic formulations of alendronate are more poorly tolerated than the proprietary preparations which results in significantly poorer adherence and thus effectiveness. Poorer effectiveness may result from faster disintegration times of many generics that increase the likelihood of adherence of particulate matter to the oesophageal mucosa. Unfortunately, market authorisation, based on the bioequivalence of generics with a proprietary formulation, does not take into account the potential concerns about safety. The poor adherence of many generic products has implications for guideline development, cost-effectiveness and impact of treatment on the burden of disease. CONCLUSIONS: The impact of generic bisphosphonates requires formal testing to re-evaluate their role in the management of osteoporosis.